Mapping ET in southeastern Colorado using a surface aerodynamic temperature model - Chávez, José L., author; Straw, Dale, author; Garcia, Luis A., author; Ley, Thomas W., author; Andales, Allan A., author; Simmons, Lane H., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Accurate estimates of spatially distributed evapotranspiration (ET) using remote sensing inputs could help improve crop water management, the assessment of regional drought conditions, irrigation efficiency, ground water depletion, and the verification of the use of water rights over large irrigated areas. In this study, ET was mapped using surface reflectance and radiometric temperature images from the Landsat 5 satellite in a surface energy budget algorithm driven by a surface aerodynamic temperature (SAT_ET) model. The SAT_ET model was developed using surface temperature, horizontal wind speed, air temperature and crop biophysical characteristic measured over an irrigated alfalfa field in Southeastern Colorado. Estimates of the remote sensing-based ET for a 4.0 hectare alfalfa field and a 3.5 hectare oats field, during the 2009 cropping season, were evaluated using two monolithic weighing lysimeters located at the Colorado State University Arkansas Valley Research Center (AVRC) in Rocky Ford, Colorado. Although the overall model performance was encouraging, results indicated that the SAT_ET model performed well under dry atmospheric and soil conditions and less accurately under high air relative humidity and soil water content conditions. These findings are evidence that SAT_ET needs to be further developed to perform better under a range of environmental and atmospheric conditions.
Meeting irrigation demands in a water-challenged environment
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.